A modelling and experimental study on the co-precipitation of Ni0.8Mn0.1Co0.1(OH)2 as precursor for battery cathodes. (8th June 2022) - Para, Maria Laura; Alidoost, Mojtaba; Shiea, Mohsen; Boccardo, Gianluca; Buffo, Antonio; Barresi, Antonello A.; Marchisio, Daniele
Highlights: Coprecipitation of Ni0.8 Mn0.1 Co0.1 (OH)2 from soluble metal salts is investigated. Mixing is controlled via a Multi-Inlet Vortex Mixer (MIVM). Nucleation, growth and agglomeration are identified as key phenomena. A population balance model is developed to simulate the coprecipitation process. Coprecipitation conditions affect particle morphology, crystallinity & size distribution. Abstract: A multi-inlet vortex mixer is used to investigate the co-precipitation of Ni0.8 Mn0.1 Co0.1 (OH)2 particles, largely employed to produce Li-ion battery cathodes. The co-precipitation process is simulated with a population balance model, adopted to describe the experimental findings and gain deeper understanding of the process. Experiments and simulations are carried out under different operating conditions to quantify the effect of mixing conditions, turbulence and feed reactant concentrations on the final characteristics of the obtained particles, such as the size distribution, structure, morphology and density. These characteristics are measured by conducting static light-scattering, FESEM and XRD analyses and are expected to have, in turn, a tremendous effect on the final electrochemical performance of the cathode. Based on the experimental and modelling observations, we discuss the role of nucleation, molecular growth and aggregation in the co–precipitation process. Eventually a possible mechanism explaining the formation of Ni0.8 Mn0.1 Co0.1 (OH)2 particles is proposed.